Long‐term stem inventory data from tropical rain forest plots in Australia: Ecological Archives E095‐209. Issue 8 (1st August 2014) - Bradford, Matt G.; Murphy, Helen T.; Ford, Andrew J.; Hogan, Dominic L.; Metcalfe, Daniel J.
Abstract : We present repeated stem measurement data from 20 0.5‐ha (100 × 50 m) permanent rain forest plots in northern Queensland, Australia, from 1971 to 2013. The plots have a rainfall range of 1200 to 3500 mm, represent 11 vegetation types, six parent materials, and range from 15 to 1200 m above sea level. Except for minor disturbances associated with selective logging on two plots, the plots were established in old growth forest and all plots have thereafter been protected. Plots were regularly censused and at each census the diameter at breast height (DBH) of all stems ≥10 cm DBH were recorded. Data is presented for 10 998 individual stems with plot stem densities at establishment ranging from 476 to 1104 stems/ha. Due to the wide geographical range of the plots, no species dominate, although the families Lauraceae, Rutaceae, and Myrtaceae contribute a large number of species. Basal area values at establishment ranged from 28.6 to 63.3 m 2 /ha and showed no trend of increasing or decreasing over time due mainly to regular disturbance and recovery from natural events such as cyclones. In addition to stems ≥10 cm DBH data, we present height data, floristic data from understory stems (≥50 cm height to <10 cm DBH), an auxiliary species list (including vines, epiphytes, ferns, grasses, herbs, and other life forms), and a list of voucher specimens lodged in herbaria. The data collected from the 20 plots provides an insight into the floristics, structure, and long‐term forest dynamics of Australian tropical rain forests and allows direct comparisons to be made with long‐term monitoring plots at a global scale.